Clumped Isotopes Link Older Carbon Substrates With Slower Rates of Methanogenesis in Northern Lakes. Issue 6 (17th March 2020) - Douglas, Peter M. J.; Gonzalez Moguel, Regina; Walter Anthony, Katey M.; Wik, Martin; Crill, Patrick M.; Dawson, Katherine S.; Smith, Derek A.; Yanay, Ella; Lloyd, Max K.; Stolper, Daniel A.; Eiler, John M.; Sessions, Alex L.
Abstract: The release of long‐stored carbon from thawed permafrost could fuel increased methanogenesis in northern lakes, but it remains unclear whether old carbon substrates released from permafrost are metabolized as rapidly by methanogenic microbial communities as recently produced organic carbon. Here, we apply methane (CH4 ) clumped isotope (Δ18 ) and 14 C measurements to test whether rates of methanogenesis are related to carbon substrate age. Results from culture experiments indicate that Δ18 values are negatively correlated with CH4 production rate. Measurements of ebullition samples from thermokarst lakes in Alaska and glacial lakes in Sweden indicate strong negative correlations between CH4 Δ18 and the fraction modern carbon. These correlations imply that CH4 derived from older carbon substrates is produced relatively slowly. Relative rates of methanogenesis, as inferred from Δ18 values, are not positively correlated with CH4 flux estimates, highlighting the likely importance of environmental variables other than CH4 production rates in controlling ebullition fluxes. Plain Language Summary: There is concern that carbon from thawed permafrost will be emitted to the atmosphere as methane (CH4 ). It is currently uncertain whether old organic carbon from thawed permafrost can be converted to CH4 as rapidly as organic carbon recently fixed by primary producers. We address this question by combining radiocarbon and clumped isotope measurements of CH4 from lakes in permafrost landscapes. Radiocarbon ( 14 C) measurements indicate the age of CH4 carbon sources. We present data from culture experiments that support the hypothesis that clumped isotope values are dependent on microbial CH4 production rate. In lake bubble samples, we observe a strong correlation between these two measurements, which implies that CH4 formed from older carbon is produced relatively slowly. We also find that higher rates of CH4 production, as inferred from clumped isotopes, are not linked to higher rates of CH4 emissions, implying that variables other than CH4 production rate strongly influence emission rates. Key Points: Experimental results indicate CH4 clumped isotopes are controlled by rates of microbial CH4 production Paired clumped isotopes and 14 C measurements imply CH4 formed from older substrates in northern lakes is produced relatively slowly Comparison of clumped isotope data and flux estimates suggests that CH4 production rate is not a strong determinant of CH4 ebullition flux